LAPORAN BIAYA KUALITAS SEBAGAI UPAYA PENGENDALIAN KUALITAS PRODUK DALAM RANGKA MENINGKATKAN DAYA SAING PERUSAHAAN - SUTANTO, STANLEY BOBBY (Berkala Ilmiah Mahasiswa Akuntansi)
Improving the quality of management in an effort to help improve the competitiveness of enterprises, as well as help the company remain competitive and continue to exist in a highly competitive business world. Companies can use to report the cost of quality control and quality cost information can be used by managers to assist in decision making. The company is not only concerned with such a large volume of sales in order to achieve maximum benefit, but should be more oriented towards improving the quality of products that can give satisfaction to the consumer. Consumer satisfaction is obtained from the company's efforts to improve the quality and control of product quality. With the company's ability to provide satisfaction to the consumer who buys a quality product, then in the long run the company will achieve optimal benefit. Thus the company can improve the competitiveness of enterprises in terms of sales and market share gains.